2017
DOI: 10.1080/14767058.2017.1390560
|View full text |Cite
|
Sign up to set email alerts
|

The short-term effect of smoking on fetal ECG

Abstract: Demonstrable by the electrophysiological methods, smoking has a direct effect on fetal cardiac function. The fetal heart rate variability shows a pattern during smoking which is a typical sign of stress conditions among adults. The results may have educational consequences as well. Understanding those, hopefully will help pregnant women give up this harmful addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Consistent with the initial report, the current reanalysis of this data set showed larger values of the category lAMP. -Acute maternal cigarette smoking reduced fetal HRV (Graca et al, 1991;Peterfi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the initial report, the current reanalysis of this data set showed larger values of the category lAMP. -Acute maternal cigarette smoking reduced fetal HRV (Graca et al, 1991;Peterfi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies reporting the effects of PTE on HR and HRV have also demonstrated mixed results. Prior studies have either reported an increase in fetal HR from acute exposure to maternal smoking ( Quigley et al, 1979 ; Kelly et al, 1984 ; Péterfi et al, 2019 ) or no statistically significant difference in fetal HR after acute exposure to maternal smoking ( Barrett et al, 1981 ; Goodman et al, 1984 ; Oncken et al, 2002 ). Additionally, prior studies have reported decreased HRV in response to acute maternal smoking ( Eriksen et al, 1984 ; Goodman et al, 1984 ; Péterfi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have either reported an increase in fetal HR from acute exposure to maternal smoking ( Quigley et al, 1979 ; Kelly et al, 1984 ; Péterfi et al, 2019 ) or no statistically significant difference in fetal HR after acute exposure to maternal smoking ( Barrett et al, 1981 ; Goodman et al, 1984 ; Oncken et al, 2002 ). Additionally, prior studies have reported decreased HRV in response to acute maternal smoking ( Eriksen et al, 1984 ; Goodman et al, 1984 ; Péterfi et al, 2019 ). Investigations of fetal HR and HRV in chronic maternal smokers reported decreased baseline fetal HR compared to controls and reduced HRV ( Kapaya et al, 2014 ; Spyridou et al, 2017 ; Zeskind and Gingras, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Measures of change in fetal autonomic system (ANS) activity, which is modulated by fetal behavioral state, serve as a practical and non-invasive index for assessment of fetal brain functional development. These measures have also been implemented to study the impact of maternal clinical disorders, exposures, or other occurrences during gestation such as maternal depression (13), maternal stress (14), maternal smoking (1519), maternal alcohol consumption (2023), and the effect of aerobic exercise on the developing fetus (24). Measures of HR, HRV, and movement vary significantly by fetal behavioral state (25, 26), therefore accounting for state is imperative for the identification of potential developmental abnormalities.…”
mentioning
confidence: 99%